Creatine supplementation in endurance sports - Engelhardt, M.; Neumann, G.; Berbalk, A.; Reuter, I. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: Creatine is a physiologically active substance indispensable to muscle contraction. The increase in creatine phosphate obtained by supplementation is greater than the increase in total creatine achieved by specific sports training. Less well-trained people can produce an immediate energy store when supplementing creatine such as is otherwise achieved by top athletes on normal nutrition by means of speed and power training. The publications so far available indicate that creatine accumulation in muscle was accomplished using relatively high doses (20 g daily over 5 d). The objective of our study was to investigate the alterations in creatine and creatinine concentrations following lower dosages. METHODS: As intermediate and finishing spurts under anaerobic conditions are gaining in importance in endurance sports, we created a special exercise test for triathletes combining endurance and interval performance. After a pretreatment exercise test was performed, the athletes ingested 6 g of creatine daily, divided into two portions for 5 d. On day 6, another exercise test was performed. RESULTS: Creatine supplementation was found to have no influence on the cardiovascular system, oxygen uptake, and blood lactate concentration. The fall in blood glucose during the exercise test was significantly reduced after consumption of creatine. Although interval power performance was significantly increased by 18%, endurance performance was not influenced. CONCLUSIONS: We conclude that creatine supplementation at doses of 6 g daily has positive effects on short-term exercise included into aerobic endurance exercise.